Identifying ribozyme-accessible sites using NUH triplet-targeting gapmers - Mir, Alain A. (Oxford University Press, 2001)
Accurately identifying accessible sites in RNA is a critical prerequisite for optimising the cleavage efficiency of hammerhead ribozymes and other small nucleozymes. Here we describe a simple RNase H-based procedure to rapidly identify hammerhead ribozyme-accessible sites in gene length RNAs. Twelve semi-randomised RNA–DNA–RNA chimeric oligonucleotide probes, known as ‘gapmers’, were used to direct RNase H cleavage of transcripts with the specificity expected for hammerhead ribozymes, i.e. after NUH sites (where H is A, C or U). Cleavage sites were identified simply by the mobility of RNase H cleavage products relative to RNA markers in denaturing polyacrylamide gels. Sites were identified in transcripts encoding human interleukin-2 and platelet-derived growth factor. Thirteen minimised hammerhead ribozymes, miniribozymes (Mrz), were synthesised and in vitro cleavage efficiency (37°C, pH 7.6 and 1 mM MgCl(2)) at each site was analysed. Of the 13 Mrz, five were highly effective, demonstrating good initial rate constants and extents of cleavage. The speed and accuracy of this method commends its use in screening for hammerhead-accessible sites.